Service Quality and Customer Satisfaction in Ethnic Cuisine: Insights from a Nasi Kebuli Restaurant in Indonesia - Puspita Dewi; Ratih Amelia; Devia Febrina; Jimmy Kelana; Debora Tambunan (Yayasan Bina Bisnis Nusantara Medan, 2025)
This study explores the influence of service quality on customer satisfaction at Rumah Makan Nasi Kebuli in Pangkalan Brandan, Indonesia. Utilizing a quantitative research approach, data were gathered through observations, questionnaires, and interviews with a selected portion of the restaurant’s customer base. The analysis employed simple linear regression using statistical software. The results indicate a significant and positive relationship between service quality and customer satisfaction. Service quality was found to be a dominant factor influencing satisfaction levels, with most of the variation in customer satisfaction explained by this variable. The findings highlight the crucial role of service quality in shaping the overall dining experience. It is recommended that the restaurant management continue to prioritize service quality improvements as a strategic effort to enhance customer loyalty and attract more visitors.